Entre-Fictions - Carrayrou, Stéphane; Michelin, Nicolas; Centre d'Art Contemporain de Rueil-Malmaison, Rueil-Malmaison (Arles : Actes Sud, 1998)
Boursier-Mougenot, Céleste ; Courbot, Didier ; Creten, Johan ; David, Franck ; Fauguet, Richard ; Gadenne, Bertrand ; Gautel, Jakob ; Guelton, Bernard ; Jézéquel, Claire-Jeanne ; Karaïndros, Jason ; Kopp, Jan; Paris, Guillaume ; Pouvreau, Paul ; Tan, Fiona ; Vaesen, Frédéric
Entre-fictions, Centre d'Art Contemporain de Rueil-Malmaison, Rueil-Malmaison, 18 avril - 16 mai 1998
kunstcatalogus